PENERAPAN ALGORITMA K-MEANS CLUSTERING UNTUK SEGMENTASI BERDASARKAN KESIAPAN SELEKSI: SYSTEMATIC LITERATUR REVIEW - Imam Fakhri Muhammad; Billy Hendrik (Smart Education, 2025)
Abstract: The application of the K-means clustering algorithm as an innovative method for readiness segmentation, enabling the grouping of individuals based on their preparedness in the selection process. With the background issue of the lack of systematic methods to identify individual readiness, this study aims to develop an effective segmentation model using K-Means. The research method involves collecting relevant data and applying the K-Means algorithm to identify optimal clusters. The results show that the K-Means algorithm successfully grouped individuals into clusters according to their selection readiness, providing strategic insights for decision-makers in conducting a more accurate and efficient selection process. This study makes a significant contribution to the development of more targeted and effective selection strategies. Keyword: Selection Strategy; Readiness-Based Grouping; Data Clustering. Abstrak: Penerapan algoritma K-means clustering sebagai metode inovatif untuk segmentasi kesiapan seleksi, yang memungkinkan pengelompokan individu berdasarkan kesiapan mereka dalam proses seleksi. Dengan latar belakang permasalahan kurangnya metode sistematis untuk mengidentifikasi kesiapan individu, penelitian ini bertujuan untuk mengembangkan model segmentasi yang efektif menggunakan K-Means. Metode penelitian melibatkan pengumpulan data relevan dan penerapan algoritma K-Means untuk mengidentifikasi cluster yang optimal. Hasil penelitian menunjukkan bahwa algoritma K-Means berhasil mengelompokkan individu ke dalam cluster yang sesuai dengan kesiapan seleksi mereka, memberikan wawasan strategis bagi pengambil keputusan dalam proses seleksi yang lebih akurat dan efisien. Penelitian ini memberikan kontribusi signifikan dalam pengembangan strategi seleksi yang lebih tepat sasaran dan efektif. Kata kunci: Strategi Seleksi; Pengelompokan Berdasarkan Kesiapan; Klasterisasi Data.